2022
DOI: 10.1007/s00018-022-04150-3
|View full text |Cite
|
Sign up to set email alerts
|

A mitochondria cluster at the proximal axon initial segment controls axodendritic TAU trafficking in rodent primary and human iPSC-derived neurons

Abstract: Loss of neuronal polarity and missorting of the axonal microtubule-associated-protein TAU are hallmarks of Alzheimer’s disease (AD) and related tauopathies. Impairment of mitochondrial function is causative for various mitochondriopathies, but the role of mitochondria in tauopathies and in axonal TAU-sorting is unclear. The axon-initial-segment (AIS) is vital for maintaining neuronal polarity, action potential generation, and—here important—TAU-sorting. Here, we investigate the role of mitochondria in the AIS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 56 publications
(85 reference statements)
2
17
0
Order By: Relevance
“…Previous work in cultured mammalian neurons has indicated that mitochondria cluster at the base of the proximal axon and that this cluster is important for axo-dendritic polarity [ 30 , 31 ]. These observations prompted us to ask if C .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous work in cultured mammalian neurons has indicated that mitochondria cluster at the base of the proximal axon and that this cluster is important for axo-dendritic polarity [ 30 , 31 ]. These observations prompted us to ask if C .…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has indicated that a cluster of mitochondria at the base of the proximal axon can regulate axo-dendritic polarity in mammalian neurons [ 30 , 31 ]. Our finding that ANC-1 is required to polarize axon growth and for clustering of mitochondria to the base of the proximal axon suggested the possibility that ANC-1 could function through mitochondria to polarize axon growth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cofilin then translocates to the mitochondria, where it generates a drop in mitochondrial membrane potential, and cytochrome c release through promotion of the opening of the permeability transition pore (Kang and Woo, 2019). A very recent and interesting work has shown that a cluster of mitochondria belonging to the axon initial segment, and with particular characteristics and little motility, is important for Tau sorting (Figure 2D) (Tjiang and Zempel, 2022). It has been shown that ROS produced in mitochondria, such as H 2 O 2 , can generate Tau oligomer formation in a mouse model (Figure 2E) (Du et al, 2022).…”
Section: Tau Toxicity and Its Role In Oxidation And Redox Regulationmentioning
confidence: 99%